Determination of Phenolic Compounds, Organic Volatile Molecules and Anti-Cancer Properties in Inula Viscosa L., Viscum Album L. and Raphanus Sativus L. - DİLEK TEPE, Hafize; UĞURLU, Aslı; YAZGAN, İdris (Sakarya University Journal of Science, 2021)
The plants elecampane (Inula Viscosa L.), mistel (Viscum album L.) and black radish seed (Raphanus Sativus L.) have been used in the treatment of common diseases worldwide as part of traditional medicine for many years. Especially in Turkey, elecampane plant is commonly used as remedy of cancer. In this study, phytochemical components of these three plants were analyzed using liquid chromatography-mass spectrometer/mass spectrometer and gas chromatography-mass spectrometer techniques. Antioxidant activity of the characterized extracts were evaluated using DPPH assay, followed by biological properties were studied using MDA-MB-231 breast cancer line. Differences in the chemical compositions of the extracts resulted in alteration in antioxidant potentials, where elecampane gave the highest antioxidant activity while black radish seed extracts did not provide any meaningful results within the test period. Cytotoxicity studies showed that chemical composition is of the most prominent factor that defined the IC50 value of each extract, where pro-oxidant and antioxidant affects were observed in relation to presence of flavonoids. Mistel extract was further tested for wound healing and apoptosis tests, and the extract was obtained as a trigger for both apoptosis and wound-healing. The findings can be a basis for refinement as fractionation of the mistel and elecampane extracts so as to obtain the best mixture that can serve as strong anticancer agent mixture.
Keywords: Elecampene; mistel; phenolic compounds; LC-MS/MS; GC-MS; anticancer.; elecampene; gc-ms; phenolic compounds; Engineering (General). Civil engineering (General); Chemistry; anticancer.; mistel; lc-ms/ms; TA1-2040; QD1-999; 3. Good health